ANALISIS PENGGUNAAN KEONG EMAS SEBAGAI PAKAN UNTUK MENSUBTITUSI PELLET PADA IKAN KAKAP PUTIH (Lates calcarifer) - Siti Hadijah; Jumianti Abubakar; Andi Hamdillah; Muhammad Yunus (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2022)
White Snapper (Lates Calcarifer) has a fairly complete nutritional content, is favored by the community and has high economic value. The success of white snapper cultivation is determined by the availability of feed during maintenance. This study aims to analyze the use of gold snails as a substitute for pellet feed on the growth and survival of white snapper, by feeding gold snails, pellets and a combination of both. The research took place from July to November 2021 at the Pond and Field Laboratory of FPIK, Indonesian Muslim University in Kalibone, Pangkep. The method was a completely randomized design (CRD) with 3 treatments and 3 replications; namely Treatment A (pellets), Treatment B (conch Emas) and Treatment C (pellets and snails Emas). Parameters measured were growth rate of fish body weight and length, Specific Growth Rate (SGR), Survival, Feed Conversion Ratio (FCR). The data were analyzed using analysis of variance value (ANOVA) and further test of Least Significant Difference (LSD) was performed if the ANOVA was significant using SPSS 22 software. The results of this study showed that the treatment used had no significant effect on all parameters measured except for absolute length growth. This shows that the use of golden snails for barramundi feed can be used to substitute pellet feed which is relatively more expensive. Even in the growth parameters, the use of golden snails was better than pellet feed, although the difference in growth was not statistically significant.